BINA DESA JADA BAHRIN MANDIRI BERBASIS PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN SIPIL SAHABAT DESA - Roby Hambali (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
The new paradigm in the national education system mandated in Law Number 23 of 2003 is a local wisdom-based education unit that encourages the acceleration of development in the region based on the potential of local communities. The Department of Civil Engineering, Faculty of Engineering, Universitas Bangka Belitung as part of the education unit in question has the responsibility to carry out this mandate, which is outlined in the department's work program.The work program in question is the Bina Desa Mandiri program which is also the flagship program of the Faculty of Engineering, Universitas Bangka Belitung. In the Bina Desa Mandiri program, the Civil Engineering Department chose Jada Bahrin Village to be developed, especially in the field of infrastructure. The first activity with the theme